Aspirations professionnelles de jeunes bacheliers au Cameroun : l’influence de la pratique de l’orientation scolaire revisitée - Dong Nguetsop Frosine Merveille; Innocent Fozing (Éducation et Socialisation)
This study questions the causes of unemployment of youth in Cameroon and focused on poor assistance to students in the consolidation of their professional aspirations, guarantee of socio-professional insertion. Data collected from 181 students in Upper Sixth classes of Government Bilingual High School Bafoussam through a random sampling method and analysed by regression ordinal logistic stands out that consulting with a guidance counselor does not influence in a significant way the types of professional aspirations entertained by students. Same goes for fields of study and their openings. Initiation to self-awareness contributes in developing in students more realistic professional aspirations rather than oblique, or utopian than undefined. Information on the realities of the job market and the world of employment contributes to developing in students more realistic professional aspirations rather than oblique, or utopian than undefined. The personal qualities of a guidance counselor also contributes to developing in students more realistic professional aspirations rather than oblique, or utopian.